Sistem Sirkulasi dan Keamanan Buku pada Perpustakaan Menggunakan Radio-Frequency IDentification berbasis IoT via WhatsApp - Harlian Navi; Nuroji (Arcitech: Journal of Computer Science and Artificial Intelligence, 2025)
The book lending process in conventional libraries is still done manually, causing queues, data input errors, and lack of operational efficiency. This technology relies on desktop or web-based digital systems, without integrating IoT technology and real-time communication. Therefore, this research proposes the development of an Internet of Things (IoT)-based book lending system integrated with WhatsApp API and RFID system to improve circulation efficiency and book security. This research uses the prototyping method so that development can be adjusted iteratively to user needs. The system was tested using the black-box testing method and showed a 100% success rate in all test scenarios. This research is an application of the integration of IoT and instant messaging platforms in the context of library management, which has not been widely raised in previous studies, and produces a prototype that is applicable to the scale of educational institutions.